Brain imaging correlates of cognitive impairment in depression - Thomas, Emma J.; Elliott, Rebecca (Frontiers in Human Neuroscience, 2009)
This review briefly summarises recent research on the neural basis of cognition in depression. Two broad areas are covered: emotional and non-emotional processing. We consider how research findings support models of depression based on disrupted cortico-limbic circuitry, and how modern connectivity analysis techniques can be used to test such models explicitly. Finally we discuss clinical implications of cognitive imaging in depression, and specifically the possible role for these techniques in diagnosis and treatment planning.